Disentangling diverse responses to climate change among global marine ecosystem models. (November 2021) - Heneghan, Ryan F.; Galbraith, Eric; Blanchard, Julia L.; Harrison, Cheryl; Barrier, Nicolas; Bulman, Catherine; Cheung, William; Coll, Marta; Eddy, Tyler D.; Erauskin-Extramiana, Maite; Everett, Jason D.; Fernandes-Salvador, Jose A.; et al.
Highlights: Experimental study identifying uncertainty sources in FishMIP global model ensemble. Warming and lower trophic level (LTL) impacts on model predictions isolated. Coupling of lower and higher trophic levels a key driver of model warming response. LTL impacts driven primarily by each model's choice of LTL driver. Overall climate projections mostly a linear combination of warming and LTL impacts. Abstract: Climate change is warming the ocean and impacting lower trophic level (LTL) organisms. Marine ecosystem models can provide estimates of how these changes will propagate to larger animals and impact societal services such as fisheries, but at present these estimates vary widely. A better understanding of what drives this inter-model variation will improve our ability to project fisheries and other ecosystem services into the future, while also helping to identify uncertainties in process understanding. Here, we explore the mechanisms that underlie the diversity of responses to changes in temperature and LTLs in eight global marine ecosystem models from the Fisheries and Marine Ecosystem Model Intercomparison Project (FishMIP). Temperature and LTL impacts on total consumer biomass and ecosystem structure (defined as the relative change of small and large organism biomass) were isolated using a comparative experimental protocol. Total model biomass varied between −35% to +3% in response to warming, and -17% to +15% in response to LTL changes. There was little consensus about the spatial redistribution of biomass or changes in the balance between small and large organisms (ecosystem structure) in response to warming, an LTL impacts on total consumer biomass varied depending on the choice of LTL forcing terms. Overall, climate change impacts on consumer biomass and ecosystem structure are well approximated by the sum of temperature and LTL impacts, indicating an absence of nonlinear interaction between the models' drivers. Our results highlight a lack of theoretical clarity about how to represent fundamental ecological mechanisms, most importantly how temperature impacts scale from individual to ecosystem level, and the need to better understand the two-way coupling between LTL organisms and consumers. We finish by identifying future research needs to strengthen global marine ecosystem modelling and improve projections of climate change impacts.